Analog Curcumin, Pentagamavunon-0 (PGV-0), Induces Senescence and Increases Cytotoxic Effect of Doxorubicin on HCC 1954 Cells - Angraini, Sonia Meta; Nugraheni, Nadzifa; Meiyanto, Edy; Hermawan, Adam (Indonesian Society for Cancer Chemoprevention, 2019)
Senescence defined as an irreversible cell cycle arrest. Senescence can inhibit cancer growth and suppress the progression of cancer. Some anticancer compounds are known to have the potential to induce senescence. Senescence defence against tumor development by preventing proliferation of cells with DNA damage. The study aimed to determine the cytotoxic effects and senescence induction of Pentagamavunon-0 (PGV-0) on Human Epidermal Growth Factor Receptor 2-positive (HER2-positive) breast cancer cells, HCC 1954. Cytotoxic tests carried out with 3- (4.5-dimethylthiazzol-2yl) -2.5-tidiphenyltetrazolium (MTT) assay showed that PGV-0 exhibited a strong cytotoxic effect with a the half maximal inhibitory concentration (IC50) value of 39 μM. Treatment with IC50 in sub-doses combined with doxorubicin showed cytotoxic enhancement effects. The senescence assay using SA-β-Galactosidase showed that the PGV-0 in a single treatment was able to induce senescence with a percentage of cell senescent of 15%. The combination treatment of PGV-0 at the half dose of IC50 with doxorubicin 100 nM was able to induce senescence with the percentage of senescent cells of 25%. Moreover, PGV-0 also increased intracellular reactive oxygen species (ROS). The results of this study indicate that PGV-0 exhibits cytotoxic effect, increases cytotoxic effect of doxorubicin and induces senescence that may correlate to the increasing of intracellular ROS in 1954 HCC cells.Keywords: Pentagamavunon (PGV-0), HCC 1954, Cytotoxic, Senescence